With no lysine kinases: the key regulatory networks and phytohormone cross talk in plant growth, development and stress response - Saddhe, Ankush Ashok; Karle, Suhas Balasaheb; Aftab, Tariq; Kumar, Kundan (Plant cell reports, 2021)
With No Lysine kinases (WNKs) are a distinct family of Serine/Threonine protein kinase with unique arrangement of catalytic residues in kinase domain. In WNK, an essential catalytic lysine requisite for attaching ATP and phosphorylation reaction is located in subdomain I, instead of subdomain II, which is essentially a typical feature of other Ser/Thr kinases. WNKs are identified in diverse organisms including multicellular and unicellular organisms. Mammalian WNKs are well characterized at structural and functional level, while plant WNKs are not explored much except few recent studies. Plant WNKs role in various physiological processes viz. ion maintenance, osmotic stress, pH homeostasis, circadian rhythms, regulation of flowering time, proliferation and organ development, and abiotic stresses are known, but the mechanisms involved are unclear. Plant WNKs are known to be involved in enhanced drought and salt stress response via ABA-signaling pathway, but the complete signaling cascade is yet to be elucidated. The current review will discuss the interplay between WNKs and growth regulators and their cross talks in plant growth and development. We have also highlighted the link between the stress phytohormones and WNK members in regulating abiotic stress responses in plants. The present review will provide an overall known mechanism on the involvement of WNKs in plant growth and development and abiotic stress response and highlight its role/applications in the development of stress-tolerant plants.
Keywords: Circadian Rhythm; Plant Development; lysin; Plant Physiological Phenomena; cirkadiánní rytmus; Stress, Physiological; protein-serin-threoninkinasy; vývoj rostlin; regulátory růstu rostlin; Plant Roots; fyziologický stres; rostlinné proteiny; Kinases; kořeny rostlin; WNKs; Lysine; Protein Serine-Threonine Kinases; Plant growth and development; Plant Proteins; Abiotic stress; fyziologie rostlin; Plant Growth Regulators; Phytohormones; Arabidopsis